Analysis and Recheck of Reinforcement Scheme of Dikes in a Polder - WU Juan; ZHANG Ming; LI Yansong (Renmin Zhujiang)
The dike reinforcement project in a polder has a total length of 8 873 m.There are some local problems along the dikes,such as the insufficient crest elevation,thin dikes,insufficient stability of dike slopes,leakage of dikes,and damaged pavement on the crest,which affect the flood control safety of dikes and cannot meet the normal operation requirements.Therefore,on the basis of analyzing the present situation and problems,targeted research on dike reinforcement design is carried out,and the design principles of dike reinforcement are put forward.Moreover,we implement the design contents,including the recheck of crest elevation,reinforcement design of dike sections,anti-sliding stability recheck of dike slopes,anti-seepage and reinforcement design of dikes,and effect evaluation.The reinforcement design scheme fully considers the actual local situation,which meets the overall flood control requirements of the river basin and is compatible with the local existing flood control projects for operation.The proposed dike reinforcement design scheme has certain universality and can be used as a reference for dike reinforcement in plain areas.